Cathartic agent nephropathy based on sodium phosphate in kidney patients transplanted. Report of case - Roberto Pineda; Alejandra Molano; Adriana Flórez; Roberto D`Achiardi; Benjamín Wancjer (Revista Colombiana de Nefrología, 2016)
Sodium phosphate nephropathy consists of damage to the kidneys caused by the use of laxatives containing sodium phosphate.  Depending on the time of use of these drugs used for colonic preparation this disease can be acute or chronic. The acute condition can be cured with a suitable treatment, but the chronic condition can cause irreversible kidney damage.This case is about a patient who receives our services in the unit in Fundación Cardio Infantil in Bogotá, Colombia, with an acute kidney injurywith renal transplant being monitored. Sodium phosphate was used to be prepared the kidney for a colonoscopy.